2015
DOI: 10.1103/physrevlett.114.146404
|View full text |Cite
|
Sign up to set email alerts
|

Band Structures of Plasmonic Polarons

Abstract: Using state-of-the-art many-body calculations based on the "GW plus cumulant" approach, we show that electron-plasmon interactions lead to the emergence of plasmonic polaron bands in the band structures of common semiconductors. Using silicon and group IV transition-metal dichalcogenide monolayers (AX_{2} with A=Mo,W and X=S, Se) as prototypical examples, we demonstrate that these new bands are a general feature of systems characterized by well-defined plasmon resonances. We find that the energy versus momentu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 55 publications
7
75
0
Order By: Relevance
“…Subsequent studies revealed that this approach may also prove useful to describe the plasmon satellites of silicon [35,45], graphene [37,46], and model systems [38,39]. Recently, the application of cumulant expansion to the calculation of angleresolved spectral function of simple semiconductors highlighted the dispersive character of plasmonic satellites [41]. In particular, it was found that the simultaneous excitation of a plasmon and a hole leads to the emergence of 'plasmonic polaron bands', that are broadened replica of the valence bands blue-shifted by the plasmon energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies revealed that this approach may also prove useful to describe the plasmon satellites of silicon [35,45], graphene [37,46], and model systems [38,39]. Recently, the application of cumulant expansion to the calculation of angleresolved spectral function of simple semiconductors highlighted the dispersive character of plasmonic satellites [41]. In particular, it was found that the simultaneous excitation of a plasmon and a hole leads to the emergence of 'plasmonic polaron bands', that are broadened replica of the valence bands blue-shifted by the plasmon energy.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [17,23,24,27,29,32,36], given the renewed interest in this technique and its use in conjunction with the GWA [29,30,35,37,[41][42][43][44] it seems appropriate and timely to systematically develop and discuss the key aspects of the GW + cumulant (GW+C) theory for interpretations of the results of both the stationary and time-resolved spectroscopies. This program is carried out in Secs.…”
Section: Introductionmentioning
confidence: 99%
“…A well known example are plasma oscillations in solids that are detectable as satellites in the photoelectron spectrum. 60,61 Another one is the effect of vibrational motion of ions that provides an intrinsic mode of the material that is detectable in the electronic structure, most prominently as vibrational sidebands in optical absorption spectroscopy of molecules. 62 This is facilitated by the coupling of the electrons to the vibrational modes, also known as phonons in crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulant approach has been successful at zero T in elucidating correlation effects beyond the GW approximation of MBPT in a variety of contexts [27][28][29][30][31][32]. For example, in contrast to GW , the approach explains the multiple-plasmon satellites observed in x-ray photoemission spectra (XPS) [27,[33][34][35][36].…”
mentioning
confidence: 99%